The Winnowing Season - Woodsmall, Cindy (Colorado Springs, Colorado : WaterBrook Press, 2013)
After a tornado destroys Kings' Orchard, Rhoda Byler and the King family move from their Old Order Amish community in Pennsylvania to one in Maine, but problems from their pasts compromise their attempts to start over.
Keywords: Amish -- Fiction; Christian fiction